KEBIASAAN BELAJAR DAN PROSES BERPIKIR MATEMATIS PESERTA OLIMPIADE SAINS PROVINSI DAN NASIONAL BIDANG STUDI MATEMATIKA TINGKAT SEKOLAH MENENGAH ATAS - Nabilah Mardhiyah, - (2021)
Science Olympiad is a competition to develop the quality of education and students' abilities. In Indonesia, lack of student interest in learning mathematics has affected participation in the Mathematics Olympiad. However, there are still students--who are achievers in mathematics Olympiads at the provincial and national levels--participating in coaching, having different study habits, and having creative abilities. Therefore, this research aims to analyze study habits, characteristics of creative thinking, and problem-solving strategies of students who have participated in the Mathematics Science Olympiad. This research used a qualitative case study method, with purposive sampling data collection techniques, involving six respondents who have participated in the provincial and national math Olympiads. Then data collection was carried out through a triangulation method including written tests, questionnaires, interviews, and documentation. The results showed that the study habits variables are categorized as good. Aspects of self-confidence, interest, and curiosity, and perseverance were identified that the six respondents are classified as high criteria. Meanwhile, the flexibility aspect is classified as a very high criterion. From the aspect of fluency, two respondents are dominant which is the same as the aspect of originality; while in the aspect of flexibility there is only one respondent dominant. In the variable of problem solving-strategy, on algebra question the respondents used strategies of breaking goals and of logical thinking. Geometry problems are solved by using strategies of making diagrams, breaking goals, and logical thinking. The combinatorics problems are solved using two strategies, namely taking into account every possibility and logical thinking. Then number theory problems are solved using two strategies, i.e., breaking goals and logical thinking.